Nutritional Treatment After Discharge of Older Patients at Nutritional Risk: A Study Protocol for a Feasibility Study - Martine Kjærsgaard Nielsen; Tina Munk; Anne Marie Beck; Jacob Rosenberg; Jesper Ryg (Medicine Advances, 2026)
ABSTRACT Background Malnutrition is prevalent among older hospitalized patients, increasing the risk of complications, extended hospital stays, and reduced quality of life. Upon discharge, a nutritional gap frequently arises, leading to insufficient intake for optimal recovery. Ensuring nutritional treatment in research settings after hospital discharge has demonstrated improvements in readmission rates, muscle strength, quality of life, and nutritional status. This study aims to evaluate the feasibility and effectiveness of nutritional treatment for older patients at nutritional risk after hospital discharge in a real‐life context. Methods This is a feasibility study conducted in cooperation with nine municipalities in Denmark and included a historical control group. At hospital discharge, older patients at nutritional risk referred to the liaison team receive a customized food package. Individualized dietary counseling is provided by a hospital dietitian during follow‐up 2–4, 30, and 90 days after discharge, with municipal follow‐up offered as needed. The primary outcome is feasibility regarding the proportion of patients included, recruited, and retained for nutritional treatment. Secondary outcomes include readmissions, mortality, quality of life, appetite, muscle strength, dietary intake, weight, and muscle mass. Conclusions Older patients at nutritional risk may experience a nutritional gap at hospital discharge. Despite evidence highlighting the importance of nutritional care during the transition from hospital to home, cross‐sector initiatives have not been effectively implemented. This study will investigate the feasibility of nutritional treatment across sectors when older patients at nutritional risk are discharged. Therefore, the results of this study could contribute to establishing a model for effective large‐scale implementation.